Can women in labor give informed consent to epidural analgesia?. (25th October 2018) - Wada, Kyoko; Charland, Louis C.; Bellingham, Geoff
Abstract: There are reasons to believe that decision‐making capacity (mental competence) of women in labor may be compromised in relation to giving informed consent to epidural analgesia. Not only severe labor pain, but also stress, anxiety, and premedication of analgesics such as opioids, may influence women's decisional capacity. Decision‐making capacity is a complex construct involving cognitive and emotional components which cannot be reduced to 'understanding' alone. A systematic literature search identified a total of 20 empirical studies focused on women's decision‐making about epidural analgesia for labor pain. Our review of these studies suggests that empirical evidence to date is insufficient to determine whether women undergoing labor are capable of consenting to epidural analgesia. Given such uncertainties, sufficient information about pain management should be provided as part of prenatal education and the consent process must be carefully conducted to enhance women's autonomy. To fill in the significant gap in clinical knowledge about laboring women's decision‐making capacity, well‐designed prospective and retrospective studies may be required.